PROFILING FISIK DAN KIMIA TABLET EKSTASI YANG BEREDAR DI WILAYAH POLDA BALI DENGAN HTPTLC-DENSITOMETRI DALAM USAHA MERUNUT JALUR PEREDARANNYA - Budiartawan, I Gede; Suaniti, Ni Made; Wirasuta, I Made Agus Gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2014)
The seizures ecstasy tablets from Bali have been physical and chemical profiled. The physical characteristic of the tablets was assessed and documented. The chromatographic fingerprint has been carried out with help of the HPTLC-densitometric and the solvent of TB (cyclohexane-toluene-diethylamine, 25:3: 1 v/v). The single linkage clustering method grouped the fingerprints. Based on the physical properties, the tables were divided into 19 groups and the multivariate analysis was clustered the tablets info 6 groups based on their chemical content relationship. The amphetamine type stimulant (ATS) substances were identified in 87% of the tablets. The ATS were methylene-dioxy-methamphetamine (MDMA), methylene-dioxy-amphetamine (MDA), and ketamine. The caffeine, piperazine, and clorquinon were the chemical adjuvant, which added into the tablets. The physical and chemical profiling could be helped the authority the trace their distribution network.
Keywords: Drug profiling; Ekstasi; HPTLC-Spektrofotodensitometri